Surgical Management of Coexisting Trigeminal Neuralgia, Hemifacial Spasm, and Glossopharyngeal Neuralgia by Microasterional Approacha (Global Journal of Medical Research, 2022)
Compression of multiples cranial nerves at the entry zone in the brainstem is called hyperactive dysfunction syndrome Caused by the dolichoectasia basilar artery that compress V VII-VIII and IX cranial nerves in our patient it caused trigeminal neuralgia hemifacial spasm and glossopharyngeal neuralgia that its a very rare condition probably less than 1 of rhizopathies published There are at less 9 cases reported in the reviewed literature This case would be the 10th reported case This is the first case treated with an Microasterional approach with a backup video
Keywords: decompression surgery; hemifacial spasm; glossopharyngeal neuralgia; microasterional approach; trigeminal neuralgia